2020
DOI: 10.3389/fpsyg.2019.03041
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Function in Mild Cognitive Impairment

Abstract: It is well-established that semantic deficits are observed in mild cognitive impairment (MCI). However, the extent of impairment in different aspects of semantic function remains unclear, and may be influenced by the tasks used to assess performance. In the present study, people with MCI and cognitively healthy older adults completed a series of tasks assessing lexical access, retrieval, and recognition of semantic information, using different input and output modalities. Control participants outperformed peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Our picture description task [106] does not exert the same level of demand on recent anterograde memory while still managing to capture fluency impairments in a-mdMCI patients, in line with previous studies also implementing picture description tasks [59,83,60,64]. In light of this evidence and considering the well documented constellation of semantic and lexical processing deficits in AD [126,127,128,129,130], our results suggest a generalised, more profound deterioration of the memory system from the preclinical stages of Alzheimer's disease. Our elicitation task successfully taps onto these emerging deficits by imposing a controlled lexicosemantic setting that is also demanding on working memory for discourse building and task maintenance, testing other dimensions of memory in addition to episodic anterograde memory and verbal learning, -which are clearly impaired in these patients-avoiding thus circularity in their diagnosis, which is already based on verbal memory assessment.…”
Section: Discussionsupporting
confidence: 86%
“…Our picture description task [106] does not exert the same level of demand on recent anterograde memory while still managing to capture fluency impairments in a-mdMCI patients, in line with previous studies also implementing picture description tasks [59,83,60,64]. In light of this evidence and considering the well documented constellation of semantic and lexical processing deficits in AD [126,127,128,129,130], our results suggest a generalised, more profound deterioration of the memory system from the preclinical stages of Alzheimer's disease. Our elicitation task successfully taps onto these emerging deficits by imposing a controlled lexicosemantic setting that is also demanding on working memory for discourse building and task maintenance, testing other dimensions of memory in addition to episodic anterograde memory and verbal learning, -which are clearly impaired in these patients-avoiding thus circularity in their diagnosis, which is already based on verbal memory assessment.…”
Section: Discussionsupporting
confidence: 86%
“…[23] Taler [24] evaluated the functions of word acquisition, retrieval, and semantic information recognition in MCI patients and in elderly individuals with normal cognition, and found that the control group was superior to the MCI group in all tests, especially in the task of picture naming. Therefore, Taler believed that the picture naming test was the most likely language test item to reveal language defects in MCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no gold standard regarding what tasks to use to evaluate language function in persons at risk of developing dementia. However, what is known is that language deficits in general and specifically semantic difficulties are seen early on McCullough et al ( 2019 ), and multiple evaluation methods might be needed to assess changes in language ability (Taler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%